Plasticity in nodal root hardpan penetration, deep soil water uptake, and shoot dry matter production under soil moisture fluctuations using chromosome segment substitution lines of rice - Nguyen, Dinh Thi Ngoc; Suralta, Roel R.; Kano-Nakata, Mana; Mitsuya, Shiro; Owusu-Nketia, Stella; Yamauchi, Akira (2020)
Rainfed lowland (RFL) fields generally experience soil moisture fluctuations (SMF) and have a hardpan layer that impedes deep rooting during episodes of drought. The development of root systems in response to SMF and the ability of roots to elongate through the hardpan when it becomes relatively soft during re-watering are key rice traits to efficiently extract water at the deep soil during subsequent periods of drought. Thus, this study aimed to identify their chromosome segment substitution lines (CSSLs) from Sasanishiki and Habataki crosses, which have root plasticity exhibited in response to SMF, which enables plants to penerate the hardpan and develop deep root systems. Root plasticity was evaluated by comparing root traits between each of the 39 CSSLs and their recurrent parent, Sasanishiki, under water-stressed and well-watered 9WW control) conditions in hydroponics and soil-filled pots. Among the 39 CSSLs. three (SL34, SL35 and SL39) had similar growth as Sasanishiki under WW, but were able to produce greater shoot dry weight than their recurrent parent under transient soil moisture stress in hydroponics and soil culture. Under SMF, in the rootbox-pinboard and rootbox-hardpan systems, only SL39 showed a significantly greater root system development than Sasanishiki, SL39 also had a more enhanced root aerenchyma formation than Sasanishiki in the shallow layer during drought-rewatered conditions under SMF, possibility facilitating atmospheric O2 diffusion to the root tips. As a consequence, SL39 promoted nodal root elongation through the hardpan during rewatering and subsequent greater deep root system development to access more water from the deep soil during the drought period of SMF, relative to Sasanishiki. The results implied that SL39 can be a good genetic material to study the QTL associated with plasticity in root hardpan penetration and deep root system development in rice.
Keywords: Upland rice; Hydroponics